Key lessons to maintain continuous improvement: A case study of four companies - Luis Paipa-Galeano; César A. Bernal-Torres; Luís Mauricio Agudelo-Otálora; Yavar Jarrah-Nezhad; Heither A. González-Blanco (Journal of Industrial Engineering and Management (JIEM), 2020)
Purpose: The purpose of this paper is to analyze the conditions under which continuous improvement practices are developed and to determine what success factors and barriers affect the sustainability of these practices in order to establish strategies that reduce the risk of failure of improvement proposals in companies. Design/methodology/approach: The paper presents a rigorous review of the success factors and barriers in the implementation of continuous improvement models in companies and a multiple case study in which four successful companies located in Bogota, Colombia, were compared using Bessant's maturity model. Findings: The results suggest the existence of systematic improvement processes in the four companies analysed in favour of the improvement of business competitiveness. After a convergence exercise between the success factors identified in the literature and the routines of the evaluation model used to identify the maturity of the companies in terms of improvement, five strategic fronts were identified to achieve sustainable improvement proposals: (1)have management commit to the improvement and guarantee resources, (2) define a methodology to implement, (3) facilitate and systematize the information on the interventions, (4) design training programs and incentives to encourage employee involvement, and (5) generate a verification and control system to provide real-time feedback on the progress of the improvement actions. Research limitations/implications: This research paper was limited by the analysis of four large Colombian companies, which did not allow the generalizability of findings. Therefore, the study offers interesting insights on the empirical evidence on the lessons learned from continuous improvement practices in order to support managers on better decision making and for the academics on better understanding continuous improvement drivers. Originality/value: The present investigation provides a conceptual framework for future studies related to the sustainability of continuous improvement in industry, approaching this topic from a theoretical and practical perspective.
Keywords: 650; success factors; improvement maturity; continuous improvement; sustainability; case studies; kaizen